Spillover effects of minimum wages: Theory and experimental evidence - Marcus Dittrich; Andreas Knabe; Kristina Leipold (Center for Economic Studies and ifo Institute (CESifo), 2011)
We study the spillover effects of minimum wages in a laboratory experiment. In a bilateral firm-worker bargaining setting, we find that the introduction of a minimum wage exerts upward pressure on wages even if the minimum wage is too low to be a binding restriction. Furthermore, raising the minimum wage to a binding level increases the bargained wage above the new minimum wage level. While the Nash solution cannot explain the existence of spillover effects, the Kalai-Smorodinsky solution yields results that are qualitatively more in line with our experimental findings.
Keywords: C71; C91; J38; 330; minimum wage; bargaining; Kalai-Smorodinsky solution; labor market experiments